EFL Student Perceptions of the International Internship Program based on the Edupreneur Perspective - Reskyani Reskyani; Uswatun Hasanah; Saiful Gaffar; Abdul Rahman; Nurdin Noni (PT ARRUS Intelektual Indonesia, 2023)
This study aims to identify EFL students’ perceptions of international internship programs based on an edupreneur’s perspective. This study employs descriptive qualitative methods. There were five students involved in this study who were selected purposefully. They are EFL students who have attended international internships in Thailand. Data collection was carried out by conducting interviews. The results of this study show that the majority of students stated that this program was very useful. Both academically and non-academically. From the entrepreneur perspective, it was found that students who were involved in the internship program received a salary, facilities, and experience that could train their independence. Even though there are several problems, this is only a technical aspect that can be improved.